Frost resistance of roller compacted concrete in airport runway subjected to ethylene glycol solution. Issue 1 (7th January 2019) - Zhang, Wuman; Zhang, Jingsong; Chen, Shuhang
Abstract : Purpose: Ethylene glycol (EG) solution is a common deicing fluid of the aircrafts. Roller compacted concrete (RCC) used in the runway and the parking apron will be subjected to freeze-thaw cycles in EG solution. The purpose of this study is to find whether RCC can be damaged by the action of freeze-thaw cycles or long-term immersion in EG solution. Design/methodology/approach: Freeze-thaw cycles test and immersion test in EG solution by weight were used to accelerate the degradation of RCC. A compression test and a three-point bending test were carried out in the laboratory to evaluate mechanical properties of RCC. The changes of microstructure were monitored by using scanning electron microscopy and energy-dispersive X-ray analysis. Findings: The results show that RCC specimens have little weight change in both freeze-thaw cycles test and immersion test. The dynamic modulus of elasticity, the compressive strength and the flexural strength of RCC with 250 freeze-thaw cycles in EG solution are decreased by 4.2, 15 and 39 per cent, respectively. The compressive strength is decreased by 35 per cent after 12 months of immersion in EG solution. Micro-cracks occur and increase with the increase in freeze-thaw cycles and immersion test. Originality/value: The mass ratio of the elements in the crystal is very close to the proportion of elements in CaC2 O4 (C:O:Ca = 1:1.26:1.6). More attention should be paid to using EG in practical engineering because both the freeze-thaw cycles and the complete immersion in EG solution damage the mechanical properties of RCC.